What Duterte Portends for Philippine Foreign Policy - Heydarian, Richard Javad (2016)
Contrary to his reputation as a foul-mouthed provincial statesman, the Philippines’ incoming president Rodrigo Duterte may very well end up as a sophisticated and nuanced geopolitical player over the South China Sea disputes and oversee the revival of Philippine-China relations.